SLANG WORDS ANALYSIS IN BILLIE EILISH’S SONG LYRICS - Nasution, Dini Fitriani; Devany, Almira; Sopha, Diana (PHILOLOGY Journal of English Language and Literature, 2024)
The study was concerned with the slang word in song lyrics. The aims of the study are focused on analyzing the types of slang proposed by the theory of Chapman (2007). The descriptive qualitative method was utilized to analyze the data in this study. The data source of this research is taken from several songs from Billie Eilish. This research uses five songs, namely Bad Guy, Ocean Eyes, Bury A Friend, When The Party’s Over, and My Future. Data was collected by reading, printing, and underlining words that contained this type of data. The researcher found 20 (48,8%) data types of primary slang and 21 (51,2%) data types of secondary slang.